Carotid Atherosclerosis Severity in Unorganized Adult Population - V. S. Kaveshnikov; V. N. Serebryakova; I. A. Trubacheva; S. A. Shalnova (Рациональная фармакотерапия в кардиологии, 2019)
Aim. To study sex and age distribution of ultrasound parameters characterizing carotid atherosclerotic (CAS) severity in the unorganized urban population.Material and methods. The data obtained in Tomsk as a fragment of the ESSE-RF study are presented (n=1600; 25-64 years age; 59% – women). All participants signed informed consent. We studied CAS plaque count, both total and maximum plaque thickness and stenosis degree in the carotid arteries.Results. The general population quantitative indicators of CAS increased with age, most actively in 40-54 years in men and 45-59 years in women. At the age of 40-44 years in men, the growth of the general population indicators was due to a noticeable increase in both plaque prevalence and of CAS severity. In 45-49 years, the prevalence increased intensively, whereas in 50-54 years growth of plaque count/size indicators were more attributive. In women 45-59 years old formation of the general population indicators concerned was mostly due to steady increase in the plaque prevalence, while out of all quantitative CAS parameters the total stenosis degree only increased significantly in 50-54 years. The general population indicators of CAS severity were higher in men than in women starting up with the age of 40 and until 55 the gender effect was merely explained by the difference in the plaque prevalence.Conclusion. Features of the gender and age distribution of the quantitative parameters of CAS among the adult urban population are determined; the age periods of their most active growth are established. The presented data on the CAS severity percentile distribution can be useful as an additional tool for risk stratification and the choice of therapy/lifestyle modification tactics in people of working age. Further studies are needed to help to explain the trends and to clarify the predictive role of the indicators studied.